Determination of midazolam dose for co-induction with alfaxalone in sedated cats. (May 2019) - Lagos-Carvajal, Angie; Queiroz-Williams, Patricia; da Cunha, Anderson; Liu, Chin-Chi
Abstract: Objective: To investigate the median effective dose 50 (ED50 ) of midazolam required for endotracheal intubation when used for co-induction of anesthesia with a low dose of alfaxalone in sedated cats. Study design: Randomized up-and-down study. Animals: A group of 14 mixed-breed cats (eight males, six females), aged 5–12 years and weighing 4.4–6.8 kg. Methods: The cats were randomly assigned in a sequential allocation numbers from one to 14. Cats were sedated with dexmedetomidine (3 μg kg –1 ) and methadone (0.3 mg kg –1 ) intramuscularly. After 15 minutes, the quality of sedation was subjectively evaluated. Anesthesia induction was performed by intravenous (IV) administration of alfaxalone (0.25 mg kg –1 ) over a 60 second interval, followed by another 60 second interval, and then an IV dose of midazolam was administered over a 5 second interval. The initial midazolam dose was 0.3 mg kg –1 ; then, the midazolam dose was adjusted by ±0.1 mg kg –1 for each consecutive cat based on successful or unsuccessful endotracheal intubation of the previous animal following an up-and-down method. This sequence was followed until six nonsequential crossovers were observed. Crossover was defined as two opposite outcomes in two sequential animals. Data were analyzed using isotonic regression with bootstrapping for determination of midazolam ED50 and logistic regression for correlations ( p < 0.05). Results: Overall, six independent crossovers were found, and ED50 of midazolam was 0.08 ± 0.04 mg kg –1 . Sedation score and successful tracheal intubation had a strong positive correlation ( p  = 0.02). Conclusions and clinical relevance: This study determined that 0.08 ± 0.04 mg kg –1 of midazolam co-administered with 0.25 mg kg –1 of alfaxalone IV allowed smooth endotracheal intubation in half of the cats sedated with methadone and dexmedetomidine at the doses used in this study.